Simultaneous Quantitation of Clevidipine and Its Active Metabolite H152/81 in Human Whole Blood by LC-MS/MS: Application to Bioequivalence Study - Li, Pengfei; Wu, Haitang; Zhao, Zhixia; Du, Ping; Xu, Haitong; Liu, Hongchuan; Zhou, Yu; Yu, Weiyue; Li, Hao; Liu, Lihong (Frontiers in Chemistry, 2022)
Clevidipine is an ultrashort acting dihydropyridine calcium antagonists, which can control blood pressure accurately. It is necessary to develop a LC–MS/MS method to quantitation clevidipine and its active metabolite H152/81 for clinical pharmacokinetic study and therapeutic drug monitoring. Liquid-liquid extraction was used for sample preparation and clevidipine-d7 and H152/81-13C-d3 were chosen as isotope internal standard. The chromatographic separation was performed on an ACE Excel 2 Phenyl column (50×2.1 mm). The mass quantification was carried on the multiple reaction monitoring of the transitions of m/z 473.1→338.1, 480.1→338.1, 356.0→324.0, and 362.2→326.2 for clevidipine, clevidipine-d7, H152/81, and H152/81-13C-d3. The validated method gave an excellent linearity over a concentration range 0.1-30 ng/mL for clevidipine and 2-600 ng/mL for H152/81. Other full validated content as accuracy, precision, extraction recovery, matrix effect and stability were also investigated and showed satisfied results. It is strongly recommend that the whole blood is the first choice for clinical bioanalysis. Using the whole blood for sample analysis can reduce the whole blood volume (1 ml vs 3 ml) and shorten the time from sample collection to storage to 5 minutes, and there is no centrifugation process and precooling in the ice water bath, which can further reduce the instability caused by exposure. The method was successfully applied to a bioequivalence study of clevidipine butyrate injectable emulsion.